Mental construction and analysis at Rudolf Carnap - ديب, قمر; إبراهيم رزوق (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Carnap differed entirely from the Western philosophical tradition in his understanding of philosophy and his attitudes towards philosophical problems . He believed that these supposed problems were to a large extent the result of our inappropriate tools .They arose in confusion because of the languages that our species had developed over of life .Daily pre-science and pre-technology .These primitive tools leave us unable to articulate no to address the traditional problems of philosophy coherently ;Our inherited languages distort even more, so we find ourselves needing to invent new concepts and organize our ideas into smaller the world in scientific and systematic research. So philosophical inquiry because became, for Carnap, a kind of conceptual geometry rather than a from of inquiry or knowledge-seeking. He did not ask how things are, in Carnap's view, but rather how we want things to be. This from of ''Voluntarism'' underlies Carnap's philosophy. The optional conceptual architecture refers in many different ways to many different problems, on different scales. He applied it both to science and to larger problems of science (such as scientific language), or about the place of science in our lives. He applied it both to local reconstructions or explanations of particular concepts ( for example, and more generally, to entire language frame works and wanted the local and the global the to fit together. Terminology Evolving Over the years ,Carnap tended to think of his first engineering projects as ''rational reconstructions'' . Both aim to reconstruct or urbanize particular terms or concepts within our more primitive , ordinary languages rather than designing and developing complete languages or language frameworks. There is a gradual change in focus over the course of one's career in the aims and scope of this conceptual engineering (linguistic) .